Islam dan Demokrasi: Menelisik Akar-akar Sosio Religius - Sumbulah, Umi (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2006)
The lack of democratic experience in Islamic governance system generates the debate among Muslims thinkers on the compatibility of democracy with Islam. Nonetheless, Madinah governance which is led and built by the Prophet Muhammad based on egality, equality and participation, reflects the substance of democracy itself. The practice of democracy considers well established socio-political condition besides doctrinal and pre-requirement aspects. Equal participation between women and men in building democratic system in governance is an essential indicator for establishing democratic system in our life.